Sheep as vectors for branched broomrape (Orobanche ramosa subsp. mutelii [F.W. Schultz] Cout.) seed dispersal. Issue 2 (11th December 2014) - Ginman, Emma; Prider, Jane; Matthews, John; Virtue, John; Watling, Jennifer
<x xml:space="preserve">Abstract</x> Sheep can be vectors for the long‐distance dispersal of weeds when seed becomes attached and retained in wool or survives the gastrointestinal tract. This study aimed to determine an appropriate quarantine period for sheep that minimized the risk of the long‐distance dispersal of the seeds of branched broomrape (Orobanche ramosa L. subsp. mutelii [F.W. Shultz] Cout.), a parasitic weed. Experiments with penned sheep found that the seeds that were placed on the soil surface adhered to the wool on the thigh and belly of the sheep, with most of the seeds attaching to the feet. Most of the seeds that were applied to the belly and thigh wool detached within 2 days, although a small proportion was present after 7 days. The seeds that were introduced to the digestive tract via drenching had a peak voidance 2 days later and no seed was detected on Day 8. It is suggested that a 7 day quarantine period for sheep would be sufficient in order to reduce the risk of the internal transport of seed to acceptable levels, but a small risk of the external transport of seed on the fleece remains.